Explore the Role of the Sphingosine-1-Phosphate Signalling as a Novel Promising Therapeutic Target for the Management of Parkinson's Disease - Bisht, Manoj; Kadian, Jai Parkash; Hooda, Tanuj; Jain, Neelam; Lather, Amit; Aggarwal, Navidha (Drug Research, 2024)
Sphingosine-1-phosphate (S1P) is a cellular signalling molecule derived from sphingosine, which is a pro-apoptotic sphingolipid. Sphingolipids control various cellular actions like growth, homeostasis, and stress-related responses. The main sources of S1P in our body are erythrocytes. S1P controls both cellular mediators and other second messengers intracellularly. The S1P receptor also helps in inflammatory and neuroprotective effects (required to manage of Parkinsonʼs). A large number of anti-Parkinson drugs are available, but still, there is a need for more effective and safer drugs. S1P and its receptors could be targeted as novel drugs due to their involvement in neuro-inflammation and Parkinsonʼs. The present review effort to explore the biological role of S1P and related receptors, for their possible involvement in PD; furthermore. Overall, S1P and other related metabolizing enzymes have significant therapeutic opportunities for Parkinsonʼs disease along with other neurological disorders.
Keywords: central nervous system; neuroinflammation; neuroprotective; Parkinsonʼs disease; sphingosine 1-phosphate (S1P) signalling